Knowledge of Stroke Risk Factors among Stroke Survivors in Nigeria - Grace Vincent-Onabajo; Taritei Moses (Stroke Research and Treatment)
Background. Knowledge of stroke risk factors is expected to reduce the incidence of stroke—whether first-ever or recurrent. This study examined knowledge of stroke risk factors and its determinants among stroke survivors. Methods. A cross-sectional survey of consenting stroke survivors at two physiotherapy facilities in Nigeria was carried out. Sociodemographic and clinical data were obtained and knowledge of stroke risk factors (defined as the ability to mention at least one correct risk factor) was assessed using open-ended questionnaire. Data were treated with descriptive statistics and logistic regression analysis. Results. Sixty-nine stroke survivors (male = 72.5%; mean ± SD age = 49.7±10.6 years) participated in the study. Thirty-four (49.4%) participants had knowledge of stroke risk factors. Only educational level was significantly associated with knowledge and participants with tertiary educational qualification were about 48 times (odds ratio = 48.5; CI = 7.6–309.8; P<0.0001) more likely to be knowledgeable than those with no education. Conclusion. Less than half of the participants had knowledge of stroke risk factors. Participants with tertiary education were significantly more knowledgeable than those with lower educational qualifications. Effective means of educating stroke survivors on stroke risk factors should be identified and adopted.